2003
DOI: 10.1002/qua.10742
|View full text |Cite
|
Sign up to set email alerts
|

Parallel programming library for molecular dynamics simulations

Abstract: ABSTRACT:A parallel programming library for molecular dynamics (MD) simulations is described and applied to the recently proposed split integration symplectic method (SISM) for MD simulation. The results show that for a system of 1024 linear chain molecules with an integration step of 4.5 fs parallel execution of SISM with the particle-particle interactions (PPIs) library on 32 computers gives efficiency of 95.6%. The results also show the parallel simulation of n particles is scalable with the number of proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It was shown that SISM offers better performances in comparison with LFV for both sequential and parallel implementation. SISM performs in parallel as LFV which means the speed up is gained due to a longer time step, which can be used by SISM 20–22.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that SISM offers better performances in comparison with LFV for both sequential and parallel implementation. SISM performs in parallel as LFV which means the speed up is gained due to a longer time step, which can be used by SISM 20–22.…”
Section: Discussionmentioning
confidence: 99%
“…10 Since the processors must frequently exchange data and each simulation time step is dependent on the previous step, load balancing and fast low-latency communication is crucial for obtaining good computational performance. 11,12 Most recent parallel computers are often built as computing clusters, many of them Beowulf-type clusters of personal computers (PCs) 13 connected into a separate network serving as the primary processor interconnection. 14 The processors cannot directly access the memory on other PCs, meaning that PC clusters have a distributed-memory Multiple Instruction Multiple Data (MIMD) architecture.…”
Section: Introductionmentioning
confidence: 99%
“…13 Programs written for such a parallel architecture must use message passing for transferring all of the data among processors and care must be taken to reduce the communication time. 11,12,15 Besides parallelization, specialized processors may also be used to increase computational speed. 16,17 The MDGRAPE-2 (Molecular Dynamics Gravity Pipeline) processor is designed for the fast calculation of nonbonding interactions in MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In some problems where a significant amount of global communication is needed, e.g. molecular dynamics, , optimal performance of intracluster communication is particularly important.…”
Section: Introductionmentioning
confidence: 99%